Perustuslakikontrollista neljässä Euroopan maassa ja Suomessa - Pellonpää, Matti (Lakimies, 2025)
Control of constitutionality of legislation in Finland and four other European countries The system of constitutional review of legislation in Finland has some unique features. Finland has no Constitutional Court, and the existing courts of law (including the Supreme Court and the Supreme Administrative Court) have only a limited power of judicial review. The main review is exercised by a parliamentary Committee, the Constitutional Law Committee, which scrutinises the constitutional compatibility of Government Bills pending before the Parliament before they are adopted as laws. The rulings of the Committee have great authoritative force as interpretations of the Constitution. Courts of law do have power to assess constitutionality ex post, but only in the sense that they may conclude that there is an ”evident conflict” between a statute and the Constitution. It a court concludes that there is an evident conflict, the statute should be left without effect and the Constitution accorded priority. The article contributes to this discussion by examining constitutional review in four European countries (France, Germany, Austria, and Spain) which actually share many fundamental values (as distinct from merely paying lip service to such values) with Finland, but which, unlike this country, have relatively well-established Constitutional Courts. The author looks at possible lessons to be learned from those countries and their systems for the purpose of reinforcing the Finnish system when contemplating its reform needs. While a Constitutional Court could give certain advantages, these are such that would make the establishment of such a court necessary. The author argues that more modest changes, whereby the roles played by the Supreme Court and the Supreme Administrative Court could be enhanced, especially by the creation of a joint session consisting of Justices from both supreme courts, would suffice. Overall, while a Constitutional Court could turn out to be a workable solution for Finland as well, there are no acute problems which would require that also Finland adopt one. This being the case, any reform of the system should be based on continuity and existing structures, as well as on the interconnection between them, rather than on the creation of new structures. On obvious reform need concerns the requirement of ”evident” conflict between a statute and the Constitution, as referred to in section 106 of the Constitution. There is a growing tendency that this requirement should be abolished. Such a change would necessitate a slight amendment of the relevant section 106, (deletion of the word ”evident” but no establishment of a Constitutional Court or some other new structure).